Robust design of countercyclical capital buffer rules - Dominik Hecker; Hun Jang; Margarita Rubio; Fabio Verona (Bank of Finland, 2024)
In this paper, we design countercyclical capital buffer rules that perform robustly across a wide range of Dynamic Stochastic General Equilibrium (DSGE) models. These rules offer valuable guidance for policymakers uncertain about the most appropriate model(s) for decision-making. Our results show that robust rules call for a relatively restrained response from macroprudential authorities. The cost of insuring against model uncertainty is moderate, emphasizing the practicality of following these robust countercyclical capital buffer rules in uncertain economic environments.
urn:nbn:fi-fe2024102587177
Keywords: E32; E44; E47; E60; G20; G28; 330; countercyclical capital buffers; macroprudential policy; model comparison; structural models; model uncertainty; robust rule